Investment Management at the Indonesia Endowment Fund for Education Agency (LPDP) - Boli, Hubertus Ade Resha Raditya (JIAN (Jurnal Ilmiah Administrasi Negara), 2025)
This study aims to explain the investment management processes implemented by the Indonesia Endowment Fund for Education Agency (LPDP). Using a qualitative approach, the findings of this study highlight that LPDP has implemented a systematic and strategic approach to investment management, encompassing planning, execution, and reporting stages. In the planning phase, LPDP formulates comprehensive short-term and long-term policies that align with regulatory requirements and national development priorities. During implementation, LPDP demonstrates a strong commitment to portfolio diversification and robust risk management strategies. Investments are actively monitored through internal audits, Asset and Liability Committee (ALCO) meetings, and adherence to performance benchmarks. LPDP ensures accountability by aligning investment practices with established guidelines and leveraging routine and incidental studies to inform decision-making. The reporting process emphasizes transparency and compliance, with detailed financial and investment performance reports prepared in accordance with Government Accounting Standards (SAP). These reports provide stakeholders with insights into portfolio performance, income generation, and other important information. However, LPDP faces challenges such as inefficiencies in data coordination, reinvestment complexities, and limited expertise in advanced financial instruments. The study underscores LPDP’s pivotal role in managing public funds to advance educational and socio-economic objectives, offering insights into optimizing investment strategies within public service agencies. By identifying best practices and addressing operational challenges, this research contributes to enhancing transparency, accountability, and efficiency in public financial management.